Reduksi Udema Kaki Mencit (Mus musculus) Terinduksi Karagenan Setelah Pemberian Ekstrak Daruju (Acanthus ilicifolius L.) - Darul Ikhwan; Octavian Rachmadi; Annisa Dyah Astari Putri; Ari Widiyantoro (Pharmacon: Jurnal Farmasi Indonesia, 2020)
Acanthus ilicifolius L. is one of the mangrove plants that contain a lot of potential secondary metabolites of medicinal raw materials. People of Sambas Regency of West Kalimantan Province uses leaves extract daruju to overcome the pain in the stiff and swollen. The objective of this study was to know the antiinflammatory activity of leaves extract of daruju, in the form of edema reduction of mices feet induced carrageenan. The method used in the form of maceration and partition extraction followed by phytochemical test of crude extract and the fraction of result of partition. Furthermore, the crude extract and the fraction of the result of the partition were tested for the reduction of edema mices feet induced carrageenan. The results showed that ethyl acetate fraction had the best antiinflammatory activity because it was able to decrease the edema of mices feet by 75% at 750 mg / kg BW. Ethyl acetate fraction has the ability to reduce edema because it contains group compounds of flavonoid and terpenoid.